Barriers to postnatal care utilization during the COVID-19 pandemic: a cross-sectional study of sociodemographic and spatial factors in Mexico City - Magalhi Robledo-Clemente; Juan Carlos Silva Godínez; Juan Carlos Silva Godínez; Lucía Daniela García Montes; Jorge Valencia-Ortega; Renata Saucedo (Frontiers in Global Women's Health)
BackgroundThe COVID-19 pandemic has disrupted maternal and postnatal care globally, particularly in low- and middle-income countries. This study investigated sociodemographic, geographic, psychosocial, and obstetric factors associated with inadequate postnatal care utilization in Mexico City during the pandemic.MethodsWe conducted a cross-sectional survey among 719 postpartum women at a major obstetric hospital in Mexico City. Maternal sociodemographic data, social support (MOS survey), prenatal care quality (Kessner Index), postnatal depression (Edinburgh Scale), care satisfaction (SERVQUAL), and obstetric history were assessed. Spatial regression models evaluated associations between maternal factors, socioeconomic status (AMAI Index), and postnatal visits, incorporating geographic dependencies.ResultsSignificant spatial autocorrelation in postnatal visit frequency was observed (χ2 = 14.07; p < 0.001) indicating geographic dependencies in healthcare utilization. Higher consultation rates were associated with being a non-qualified worker (β = 0.252), living with a domestic partner (β = 0.196), and belonging to the medium-low socioeconomic group (β = 0.297). Maternal education showed no significant association. The spatial error term confirmed significant geographic dependencies (β = −0.153, p < 0.001).ConclusionsGeographic location, occupation, and socioeconomic status significantly influence postnatal visit frequency during public health crises, while education plays a lesser role. These findings suggest the need for targeted interventions addressing geographic barriers and incorporating mental health support to enhance maternal healthcare access among vulnerable populations. Future research should focus on developing integrated care frameworks that can better withstand disruptions during public health emergencies.